Alignment and authority: Federalism, social policy, and COVID-19 response. (January 2023) - Greer, Scott L.; Dubin, Kenneth A.; Falkenbach, Michelle; Jarman, Holly; Trump, Benjamin D.
Highlights: Effective pandemic response requires alignment of social policy and health policy. Federalism can create misalignment in health and social policy. More automatic and collaborative intergovernmental relations enabled alignment and effective pandemic response.